2020
DOI: 10.3389/fenrg.2020.549615
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonization in Complex Energy Systems: A Study on the Feasibility of Carbon Neutrality for Switzerland in 2050

Abstract: Decarbonization gained prominence with the witnessed rise of temperature over recent years, particularly in the aftermath of the adoption of the Paris agreement for limiting the temperature increase within 2°C until 2050. Biogenic resources are explicitly indicated as carbon-neutral from Life Cycle Assessment perspective by the IPCC, shedding light on the carbon-neutral society by applying Biogenic Energy Carbon Capture for creating negative emissions. This article proposes a novel modeling approach by introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Also worth mentioning is the work of (Gençer et al, 2020), in which they developed the SESAME-tool to evaluate and compare energy transition pathways; however, SESAME does not include optimization. In the work of Li et al (2020), they developed a new modeling approach to optimize the carbon loop of biomass and carbon capture and storage for the carbon neutrality of Switzerland in 2050. However, Li et al (2020) focus on climate change and do not include an holistic LCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also worth mentioning is the work of (Gençer et al, 2020), in which they developed the SESAME-tool to evaluate and compare energy transition pathways; however, SESAME does not include optimization. In the work of Li et al (2020), they developed a new modeling approach to optimize the carbon loop of biomass and carbon capture and storage for the carbon neutrality of Switzerland in 2050. However, Li et al (2020) focus on climate change and do not include an holistic LCA.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Li et al (2020), they developed a new modeling approach to optimize the carbon loop of biomass and carbon capture and storage for the carbon neutrality of Switzerland in 2050. However, Li et al (2020) focus on climate change and do not include an holistic LCA. Lopion et al (2018) reviewed energy system models and concluded that four elements are required to provide holistic insight for national GHG reduction strategies: 1) cross-sectoral technologies (Pregger et al, 2013;Lopion et al, 2018); 2) high temporal resolution (Lopion et al, 2018;Mallapragada et al, 2018;Victoria et al, 2019); 3) high spatial resolution (Haller et al, 2012;Lopion et al, 2018;Victoria et al, 2019); and 4) evaluating environmental impacts holistically, for which LCA is best suited (Lopion et al, 2018;Ringkjøb et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Li et al [21] also elucidated whether it is feasible to reach GHG neutrality in Switzerland, whereas the authors focused on carbon flows in the system and details on the energy flows were not revealed. In agreement with the 'Energieperspektiven 2050+', the study suggested that net-zero emissions until 2050 can be reached, however necessitates the capture of as much as 20 Mt of CO 2 , of which 14 Mt or 30% of today's emissions will be sequestrated.…”
Section: Scenarios For a Net-zero Emissions Energy Systemmentioning
confidence: 99%
“…In addition, the damage fossil fuels are causing in urban areas is causing hundreds of thousands of cases of premature deaths and respiratory illness [9]. Because of the seriousness of these issues, the Paris Climate Accord has declared a state of emergency and has called for a reduction in all carbon emissions with the goal of being carbon neutral by the year 2050 as well as declaring the objective of keeping the increase in global average temperature to well below 2°C above pre-industrial levels within this century and further to pursue efforts to limit the increase to 1.5°C [10].…”
Section: Problem Statementmentioning
confidence: 99%